2015
DOI: 10.4269/ajtmh.14-0541
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis: Dynamics of Classical Malaria Epidemics Show Plasmodium falciparum's Survival Strategy

Abstract: Abstract. Areas of marginal transmission can generate enormous lethal falciparum malaria epidemics when factors favoring the parasite shift only slightly. Although usually described in terms of vectorial capacity, medical scientists working in India in the early 20th century came to the conclusion that "an epidemic of relapses" was the key triggering event of malaria epidemics. This explanation has been largely discarded, because the biology of Plasmodium falciparum recrudescence has since been differentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Our work suggests that gametocytogenesis remains constant as infections progress from recent transmission to chronic carriage, and it is the difference in asexual survival/replication rates that promotes different gametocyte densities, independently of environmental factors. Although it has been suggested that P. falciparum investment in gametocyte production adjusts to host nutrient availability (43), drug pressure (22), transmission intensity (44), and even seasonality (45, 46), results are often inconsistent and potentially affected by the dynamics of asexual parasite growth, without necessarily indicating altered sexual commitment. In Sudan, following the long dry season, gametocyte density estimates have been reported to increase prior to the highest transmission peak (47), suggesting a higher gametocyte investment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work suggests that gametocytogenesis remains constant as infections progress from recent transmission to chronic carriage, and it is the difference in asexual survival/replication rates that promotes different gametocyte densities, independently of environmental factors. Although it has been suggested that P. falciparum investment in gametocyte production adjusts to host nutrient availability (43), drug pressure (22), transmission intensity (44), and even seasonality (45, 46), results are often inconsistent and potentially affected by the dynamics of asexual parasite growth, without necessarily indicating altered sexual commitment. In Sudan, following the long dry season, gametocyte density estimates have been reported to increase prior to the highest transmission peak (47), suggesting a higher gametocyte investment.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that P. falciparum investment in gametocyte production adjusts to host nutrient availability (54), drug pressure (24), transmission intensity (55), and even seasonality (56, 57), results are often inconsistent and potentially affected by the dynamics of asexual parasite growth, without necessarily indicating altered sexual commitment. In Sudan, following the long dry season, gametocyte density estimates have been reported to increase prior to the highest transmission peak (58), suggesting a higher gametocyte investment.…”
Section: Discussionmentioning
confidence: 99%